Lightweight Cryptographic Algorithm Analysis for Secure IoT Communication on ESP-32 Platforms - Rafat, Shihab Hossen; Jarin, Mishat Nissat; Mahdee, Taher Muhammad; Musa Miah, Abu Saleh; Haque, Najmul; Rahman Tusher, Md. Mahbubur; Shin, Jungpil; Ahmed, Istiaque (2025 International Conference on Quantum Photonics, Artificial Intelligence, and Networking (QPAIN), 2025)
His paper presents ESP-SecureFlow, a novel adaptive cryptographic framework tailored for ESP-32-based IoT devices, designed to intelligently balance security, performance, and energy efficiency in resource-constrained environments. Unlike traditional static encryption methods, ESP-SecureFlow dynamically selects between AES-128 and RC4 based on real-time system parameters such as battery level, message criticality, and computational load. A key innovation is its hybrid decision engine, which enables seamless transitions between lightweight and high-security algorithms: leveraging RC4 during low-power conditions for routine data, and enforcing AES-128 for critical transmissions or when power is abundant. Through extensive experimentation over 5,000 encryption cycles across varying message sizes (8-64 bytes), the framework demonstrates up to 23.8% reduction in power consumption compared to static AES-128 implementations, without sacrificing cryptographic robustness. Moreover, it achieves a 40.3% improvement in energy efficiency over static RC4 in critical-use scenarios, highlighting its effectiveness for adaptive security in real-world IoT deployments. These results establish ESP-SecureFlow as a practical, intelligent, and deployable solution for next-generation secure IoT systems requiring dynamic, context-aware encryption.his paper presents ESP-SecureFlow, a novel adaptive cryptographic framework tailored for ESP-32-based IoT devices, designed to intelligently balance security, performance, and energy efficiency in resource-constrained environments. Unlike traditional static encryption methods, ESP-SecureFlow dynamically selects between AES-128 and RC4 based on real-time system parameters such as battery level, message criticality, and computational load. A key innovation is its hybrid decision engine, which enables seamless transitions between lightweight and high-security algorithms: leveraging RC4 during low-power conditions for routine data, and enforcing AES-128 for critical transmissions or when power is abundant. Through extensive experimentation over 5,000 encryption cycles across varying message sizes (8-64 bytes), the framework demonstrates up to 23.8% reduction in power consumption compared to static AES-128 implementations, with-out sacrificing cryptographic robustness. Moreover, it achieves a 40.3% improvement in energy efficiency over static RC4 in critical-use scenarios, highlighting its effectiveness for adaptive security in real-world IoT deployments. These results establish ESP-SecureFlow as a practical, intelligent, and deployable solution for next-generation secure IoT systems requiring dynamic, context-aware encryption. T